Research Trend of Digital Learning Media in Science and Social Studies Based on Problem-Based Learning for Critical Thinking Skills (2020-2025) - Jihanifa, Firda Afita; Sutopo, Yeri; Subali, Bambang; Widiarti, Nuni (Papanda Publisher, 2025)
Technological advances are driving the adoption of PBL-based digital media in elementary Science and Social Studies classes to cultivate critical thinking in line with the Merdeka Belajar curriculum and 21st-century skills. This study aims to map the publication trends of Science and Social Studies digital learning media based on Problem-Based Learning (PBL) and its influence on the critical thinking skills of elementary school students between 2020 and 2025. Using a Systematic Literature Review (SLR) with the PRISMA model, the authors identified 200 articles and selected 54 based on relevance, research design, and full-text accessibility. The synthesis focused on publication trends, research methods, media types, and skill targets. Results show that: (1) research publications peaked in 2024 (35.2%); (2) the dominant method was Research & Development (61.1%), particularly the ADDIE model; (3) most developed media were interactive multimedia and animated videos (each 20.4%); (4) PBL-based digital media effectively fostered critical thinking and other 21st-century skills. The study recommends developing teacher capacity, expanding the use of integrated media designs, and revising educational policies. Future research should explore AI-based adaptive learning platforms, investigate the long-term impact of PBL digital media, and expand qualitative or mixed-method studies to capture learners' in-depth experiences and contextual engagement.